A novel 2D metal–organic framework probe: a highly sensitive and visual fluorescent sensor for Al3+, Cr3+ and Fe3+ ions. (23rd September 2022) - Shi, Min; Fu, Chenchen; Yu, Jie; Yang, Yapu; Shi, Pengfei
Abstract : A novel 2D MOF Tb-DBA was constructed. Tb-DBA could detect Al 3+, Cr 3+ and Fe 3+ ions rapidly, sensitively, selectively, reversibly and visually. Tb-DBA represents a promising material for the quick detection of metal ions in aqueous solution. Abstract : The development of metal–organic framework (MOF)-based fluorescent sensors in the detection of metal ions has attracted significant interest. In this study, a novel 2D MOF Tb-DBA was constructed using Tb 3+ and 2′-amino-1, 1′:4, 1′′-terphenyl-4, 4′′-dicarboxylic acid (H2 DBA) by a solvothermal method. Tb-DBA could detect Al 3+, Cr 3+ and Fe 3+ ions rapidly, sensitively, selectively and reversibly. The detection limit is as low as the nM level. Tb-DBA displayed fluorescence enhancement in the presence of Al 3+, Cr 3+ and Fe 3+ ions. Significantly, Al 3+, Cr 3+ and Fe 3+ ions could be visually detected under UV light. Additionally, Tb-DBA could also act as an indicator for alkaline solutions when pH > 10. The detection mechanism was studied by ICP, EDS and PXRD tests. These studies illustrated that cation exchange proceeded between Tb-DBA and Al 3+, Cr 3+ and Fe 3+ ions, which inhibited the energy transfer from DBA to Tb 3+ and enhanced the π*–π transitions of DBA.